Camshaft Failure Simulation with Static Structural Approach - Riduwan Prasetya; Andoko Andoko; Suprayitno Suprayitno (Journal of Mechanical Engineering Science and Technology (JMEST), 2021)
A failure happens within the camshaft of the minibus when the vehicle is in utilize. The camshaft was a fracture within the bearing between the primary cylinder exhaust valve and the second cylinder suction. This simulation aims to find the causes of camshaft failure utilizing the finite element method with a static structural approach, including simulations of deformation, strain, stress, fatigue life (stress-life and strain-life), and cracks. The method used in this paper is the finite element method with a static structural approach by ANSYS software. The camshaft material is a gray cast iron designed using Solidworks. Pre-processing includes meshing with a size of 3 mm. The value of loading force (1348.28 N) and torque (113400 Nmm) are fixed, and the boundary conditions are varied. Processing includes the process of computation and post-processing into a part that displays the results. The simulation results show that for all the deformation and strain values that are in the elasticity area of the material, the maximum and minimum stress which is below the strength of the material, the location of the maximum values of deformation, strain, and stress is not at the fault location. The simulation of fatigue life both in stress-life and strain-life results in infinite cycles, which is above 106 cycles, while the simulation of cracks results in a decrease in the cycle. Based on the simulation results with the above parameters to the camshaft, it was found that a failure was caused by a defect characterized by reduced fatigue life at the same loading conditions.